2021
DOI: 10.3389/fchem.2021.620589
|View full text |Cite
|
Sign up to set email alerts
|

Hydrazine-Containing Heterocycle Cytochalasan Derivatives From Hydrazinolysis of Extracts of a Desert Soil-Derived Fungus Chaetomium madrasense 375

Abstract: “Diversity-enhanced extracts” is an effective method of producing chemical libraries for the purpose of drug discovery. Three rare new cytochalasan derivative chaetoglobosins B1-B3 (1–3) were obtained from chemically engineered crude broth extracts of Chaetomium madrasense 375 prepared by reacting with hydrazine monohydrate and four known metabolite chaetoglobosins (4–7) were also identified from the fungus. The structures were identified by NMR and MS analysis and electronic circular dichroism simulation. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Previous reports have demonstrated that there is a transition between cell apoptosis and pyroptosis in cancer ( 12 , 13 ). The present study indicated that chaetoglobosin E induced cell apoptosis; thus, we further explored whether chaetoglobosin E affected pyroptosis.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Previous reports have demonstrated that there is a transition between cell apoptosis and pyroptosis in cancer ( 12 , 13 ). The present study indicated that chaetoglobosin E induced cell apoptosis; thus, we further explored whether chaetoglobosin E affected pyroptosis.…”
Section: Resultsmentioning
confidence: 94%
“…They exert a broad range of biological activities, among which their antitumor activity has been studied most extensively (10). Previously, we reported the anti-tumor activities of a series of chaetoglobosins isolated from the metabolites of Chaetomium madrasense 375 (11)(12)(13). We found that chaetoglobosin E had a more potent anti-tumor effect against A549, HCC827, SW620, and MDA-MB-231 cells compared to those of chaetoglobosin B1, B2, B3, B, D, cytoglobosin A, and cisplatin (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diversity-enhanced extracts are obtained from multiple chemical reactions that directly form new carbon–carbon bonds in the extracts of natural resources in order to afford diverse natural product–like library-bearing remodeled molecular scaffolds. Several chemical transformations of natural extracts using similar methods have been reported ( López et al, 2007 ; Ramallo et al, 2011 ; Ramallo et al, 2018 ; Solís et al, 2019 ; Salazar et al, 2020 ) ( Kawamura et al, 2011 ; Kamauchi et al, 2015 ; Tomohara et al, 2016 ; Kamauchi et al, 2018 ; Guo et al, 2021 ; Sulistyowaty et al, 2021 ), but most of the methods simply provide compounds in which some functional groups have been transformed. However, we have defined diversity-oriented extracts as those natural extracts formed by reactions that produce multiple diversities similar to that observed in diversity-oriented synthesis, including the formation of new carbon–carbon bonds, modification of molecular scaffolds ( Oshima and Kikuchi, 2018 ), and conversion of functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…Several chemical transformations of natural extracts using similar methods have been reported (López et al, 2007;Ramallo et al, 2011;Ramallo et al, 2018;Solís et al, 2019;Salazar et al, 2020) (Kawamura et al, 2011;Kamauchi et al, 2015;Tomohara et al, 2016;Kamauchi et al, 2018;Guo et al, 2021;Sulistyowaty et al, 2021), but most of the methods simply provide compounds in which some functional groups have been transformed. However, we have defined diversity-oriented extracts as those natural extracts formed by reactions that produce multiple diversities similar to that observed in diversity-oriented synthesis, including the formation of new carbon-carbon bonds, modification of molecular scaffolds (Oshima and Kikuchi, 2018), and conversion of functional groups.…”
Section: Introductionmentioning
confidence: 99%